Clinico-epidemiologic profile and perinatal outcome of patients with oligohydramnios in third trimester in a tertiary care hospital - Bumrah , Sunaina; Grover, Seema; Kaur , Khushpreet; Rajora, Parveen; Tapasvi, Isha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Oligohydramnios has an incidence of around 1-5% of total pregnancies. It is associated with adverse perinatal outcomes like preterm delivery, low birth weight, foetal distress, and passage of meconium and NICU admission. Aims and objectives were to study the risk factors associated with oligohydramnios in pregnancy and to evaluate the perinatal outcome in patients with oligohydramnios. Methods: The present study was a prospective observational study of six months, which included 60 patients with gestational age >28 weeks, selected after verifying the inclusion and exclusion criteria. A detailed history and clinical examination done and relevant investigations sent. Patients were followed up postpartum till discharge from hospital. Results: The prevalence of oligohydramnios is found to be 8.5% in our study and there were more primigravida (55%). Oligohydramnios was idiopathic in 50% of our patients, followed by presence of hypertensive disorders in 20%. Caesarean delivery was required in 48.3% of the patients. In terms of perinatal outcome, 46.6% of the babies were low birth weight, 38.3% preterm, NICU admission in 26.6% and stillbirth rate was found to be 6.6%. Conclusions: Oligohydramnios was an isolated finding in half of the cases and in these only adverse perinatal outcome noted was small for gestational age. When associated with risk factors, oligohydramnios was associated with increased perinatal morbidity and mortality in terms of prematurity, foetal distress, low birth weight, NICU admission, stillbirth.